2014
DOI: 10.1177/1097184x14539511
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Masculinities in the Context of Social Change

Abstract: Through analysis of fifty in-depth interviews with married men from different socioeconomic backgrounds and ages in seven provinces in Turkey, this article examines the internal dilemmas and contradictions in the construction of masculine identities in the context of social change in the country. The focus is on men's experiences of most salient relational contexts with their parents, their children, and their spouses, and the possible implications of these relational experiences as well as prevailing social d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…This findings of this study are congruent with other recent research findings in Turkey and agree with the basic assumptions of family theorizers (Ataca, 2009;Boratav, Fişek, & Ziya, 2014, 2017Çelik, 2019;Sunar, 2005). Underlining that child-parent relationships in Turkish families are multi-dimensional, Fişek (2018) reported that there is typically very strong and intense emotional exchange and enmeshment between mother and child, while there is a distance derived from the structural hierarchy between father and child.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This findings of this study are congruent with other recent research findings in Turkey and agree with the basic assumptions of family theorizers (Ataca, 2009;Boratav, Fişek, & Ziya, 2014, 2017Çelik, 2019;Sunar, 2005). Underlining that child-parent relationships in Turkish families are multi-dimensional, Fişek (2018) reported that there is typically very strong and intense emotional exchange and enmeshment between mother and child, while there is a distance derived from the structural hierarchy between father and child.…”
Section: Discussionsupporting
confidence: 93%
“…Recent research studies report that the dynamics of father-child relationships have changed (Floyd & Morman, 2005;Boratav et al, 2017;Morman & Floyd, 2006;Sunar, 2002), but fathers in Turkey still remain distant from their children and communicate less (maintaining a more distant relationship tends to limit communication), compared to the mothers, in order to avoid spoiling the children or allowing them to be disrespectful (Ataca, Kağıtçıbaşı & Diri, 2007;Boratav et al, 2014;Barutç u & Hıdır, 2016;Sunar, 2009;Çelik & Bulut, 2019). Research findings also show that these qualities of fatherhood are associated with traditional/authoritarian behavior, and that they influence father-child relationships in a negative way (Bulanda, 2004;Gaertner, Spinrad, Eisenberg & Greving, 2007;Paquette, Bolte, Turcotte, Dubeau & Bouchard, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Masculinity is not monolithic (Connell 2005); even in a single sociocultural context there are multiple ways of being masculine and performing masculinity. The gap between hegemonic masculine ideals and men's actual practices and experiences, as well as the varied contextual and TALKING POLITICS, PERFORMING MASCULINITIES 7 structural conditions men face, means that contradictions and compromises are inevitable (Boratav et al 2014;Choi and Peng 2016) and is indicative of the potential for change and fluidity in the meanings and practices of masculinity (Johansson and Ottemo 2015;Kimmel 2005;Messerschmidt 2012). Those who are unable to aspire to idealized or dominant standards of masculinity can find alternative way of being men.…”
Section: Masculinities As Contextualized Social Practicesmentioning
confidence: 99%
“…Studies of masculinity have demonstrated increasing awareness of intersectionality, the interconnection between gender and other social divisions such as class, race, and sexuality (Pompper 2010), and the multiplicity of masculinities across different local contexts (Beasley 2008;Boratav et al 2014;Lusher and Robbins 2009). In one of the few studies to have focused on the interaction between politics and gender, Strier (2014, p. 4) focused on the fathers of children who were "disappeared" by the Argentinian government between 1976 and 1983.…”
Section: Masculinities As Contextualized Social Practicesmentioning
confidence: 99%
“…The first author has been residing and researching in Norway since the early 1990s, specializing in comparative gender and social policy analyses, including comparative studies of Turkey and Norway(Sümer, 2004(Sümer, , 2009(Sümer, , 2014Sümer et al, 2014). The second author situates herself as a Turkish feminist, educated in Turkey, the United States and Europe, specializing in comparative studies of women's activism and gender studies(Bolak-Boratav et al, 2014;Eslen-Ziya, 2013;Eslen-Ziya and Erhart, 2015). 2.…”
mentioning
confidence: 99%